A Review of Problem Solving Techniques in Engineering Project Management - Mapping The Mind, Design Thinking Approach and Six Thinking Hats - Othman, Mohd Hilmi; Bamasood, Mohammed (Journal of Advanced Mechanical Engineering Applications, 2021)
In order to effectively manage and run a successful organization, problem-solving techniques are important for the successful leader/project manager. This paper introduced three problem-solving techniques in engineering project management which are Mapping the Mind, Design Thinking Approach, and Six Thinking Hats Methods. The objective of this paper is to review these three techniques, which consist of the descriptions of the techniques, the advantages/disadvantages, the highlights and the addition of suggestions, comments and analysis/comparison between the three techniques. This review had been made from various types of information, back in year 2000 until present which is year 2020. This article can be a good reference for engineering project managers, to be used by their project management team members, in order to solve associated problems during engineering processes or services.